Proof of concept blockchain for version control - Leow, Zheng Xu (2019)
Blockchain technology was oftentimes known as a decentralized system, with no involvement of a third party or centralized trusted entity to oversee the movement of currency. However, most of the blockchain technology is developed as a new digital form of transaction currency known as cryptocurrency. Currently, developers are trying to use blockchain technology to increase the efficiency of their development as opposed to cryptocurrency. In this research, a proof of concept was made to understand the difference between using blockchain technology as a cryptocurrency compared to a commercial application such as Git which is a version control software. The proposed concept was to use blockchain as an index for storing the root hash of a directory to apply the three main functions of Git which are pull, push and commit. This concept would give developers an understanding of how blockchain can be developed as an application. Results from this research would allow developers to have a clearer picture to understand the uses of blockchain technology in applications that do not involve transactions.